Genome sequence of the date palm Phoenix dactylifera L - Al-Mssallem, Ibrahim S. (Nature Pub. Group, 2013)
Date palm (Phoenix dactylifera L.) is a cultivated woody plant species with agricultural and economic importance. Here we report a genome assembly for an elite variety (Khalas), which is 605.4 Mb in size and covers >90% of the genome (~671 Mb) and >96% of its genes (~41,660 genes). Genomic sequence analysis demonstrates that P. dactylifera experienced a clear genome-wide duplication after either ancient whole genome duplications or massive segmental duplications. Genetic diversity analysis indicates that its stress resistance and sugar metabolism-related genes tend to be enriched in the chromosomal regions where the density of single-nucleotide polymorphisms is relatively low. Using transcriptomic data, we also illustrate the date palm’s unique sugar metabolism that underlies fruit development and ripening. Our large-scale genomic and transcriptomic data pave the way for further genomic studies not only on P. dactylifera but also other Arecaceae plants.